Effectiveness and impact of a reduced infant schedule of 4CMenB vaccine against group B meningococcal disease in England: a national observational cohort study. Issue 10061 (3rd December 2016) - Parikh, Sydel R; Andrews, Nick J; Beebeejaun, Kazim; Campbell, Helen; Ribeiro, Sonia; Ward, Charlotte; White, Joanne M; Borrow, Ray; Ramsay, Mary E; Ladhani, Shamez N
Summary: Background: In September, 2015, the UK became the first country to introduce the multicomponent group B meningococcal (MenB) vaccine (4CMenB, Bexsero) into a publicly funded national immunisation programme. A reduced two-dose priming schedule was offered to infants at 2 months and 4 months, alongside an opportunistic catch-up for 3 month and 4 month olds. 4CMenB was predicted to protect against 73–88% of MenB strains. We aimed to assess the effectiveness and impact of 4CMenB in vaccine-eligible infants in England. Methods: Public Health England (PHE) undertakes enhanced surveillance of meningococcal disease through a combination of clinical, public health, and laboratory reporting. Laboratory-confirmed cases of meningococcal disease are followed up with PHE local health protection teams, general practitioners, and hospital clinicians to collect demographic data, vaccination history, clinical presentation, and outcome. For cases diagnosed between Sept 1, 2015, and June 30, 2016, vaccine effectiveness was assessed using the screening method. Impact was assessed by comparing numbers of cases of MenB in vaccine-eligible children to equivalent cohorts in the previous 4 years and to cases in vaccine-ineligible children. Findings: Coverage of 4CMenB in infants eligible for routine vaccination was high, achieving 95·5% for one dose and 88·6% for two doses by 6 months of age. Two-dose vaccine effectiveness was 82·9% (95% CI 24·1–95·2) against all MenB cases, equivalent to a vaccine effectiveness of 94·2% against the highest predicted MenB strain coverage of 88%. Compared with the prevaccine period, there was a 50% incidence rate ratio (IRR) reduction in MenB cases in the vaccine-eligible cohort (37 cases vs average 74 cases; IRR 0·50 [95% CI 0·36–0·71]; p=0·0001), irrespective of the infants' vaccination status or predicted MenB strain coverage. Similar reductions were observed even after adjustment for disease trends in vaccine-eligible and vaccine-ineligible children. Interpretation: The two-dose 4CMenB priming schedule was highly effective in preventing MenB disease in infants. Cases in vaccine-eligible infants halved in the first 10 months of the programme. While ongoing national surveillance will continue to monitor the longer-term impact of the programme, these findings represent a step forward in the battle against meningococcal disease and will help reassure that the vaccine protects against this deadly infection. Funding: Public Health England.